EFFECTIVE TREATMENT OF PATIENTS WITH CHRONIC HEART FAILURE AND DEPRESSIVE DISORDERS WITH NOOTROPICS DRUG PANTOGAM ACTIV - A. P. Baranov; A. V. Strutynsky; O. Sh. Oynotkinova; E. V. Gorbacheva; V. V. Trishina; A. S. Gusev-Scherbakov; J. J. Golubev (Архивъ внутренней медицины)
We investigate the efficiency of the inclusion nootropic drug Pantogam Activ in the complex therapy of 82 patients with heart failure, ischemic heart diseases, anxiety and depressive disorders. It was shown that an 8-week treatment with Pantogam Activ in most patients is accompanied by a significant reduction of anxiety and depressive disorders, increase exercise tolerance, improved autonomic regulation of heart function and decrease the frequency of supraventricular and ventricular arrhythmias, which is accompanied by a marked improvement in the quality of life.